2021
DOI: 10.1101/2021.01.12.426210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to fruit-flavoring during adolescence increases nicotine consumption and promotes dose escalation

Abstract: The rise of e-cigarette popularity has sparked interest in the role of palatable flavors on nicotine use. Despite growing evidence that sweet flavorants enhance nicotine reward, their influence on nicotine consumption has not been studied extensively. In addition, the impact that flavored nicotine use in adolescence could have on nicotine reward and dependence in adulthood remains unclear. This study examined the role of flavored nicotine access on nicotine preference and consumption longitudinally, from adole… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(69 reference statements)
1
0
0
Order By: Relevance
“…A recent report also revealed that adolescent male rats displayed larger shifts in preference behavior than adult males using a shorter puff duration than was used in the present study (Frie et al, 2020). Another study found that adolescent female mice escalated their consumption of a flavored nicotine solution as compared to adolescent male mice (Patten et al, 2021). Together with existing work, the present findings suggest that the discriminative stimulus and reinforcing effects of nicotine are enhanced in adolescent female rats.…”
Section: Control Nicotinesupporting
confidence: 80%
“…A recent report also revealed that adolescent male rats displayed larger shifts in preference behavior than adult males using a shorter puff duration than was used in the present study (Frie et al, 2020). Another study found that adolescent female mice escalated their consumption of a flavored nicotine solution as compared to adolescent male mice (Patten et al, 2021). Together with existing work, the present findings suggest that the discriminative stimulus and reinforcing effects of nicotine are enhanced in adolescent female rats.…”
Section: Control Nicotinesupporting
confidence: 80%